A note on workplace psychopathic bullying – Measuring its frequency and severity - Boddy, C.; Taplin, Ross (Pergamon, 2017)
© 2017 Elsevier Ltd In this short paper we discuss methods of measurement for investigating bullying under workplace psychopaths. We find that past estimates of bullying under workplace psychopaths may be too low due to the use of inadequate scales. We conclude that the use of actual numerical values is preferential for measuring psychopathic bullying due to the highly skewed nature of the results. Further, non-numerical measures of the severity of bullying may also need to adopt extreme end point descriptors in order to capture the severe violence of the threats that may be made by a psychopathic manager.